Advanced microeconomic theory - Jehle, Geoffrey J. (Readings, Mass : Addison-Wesley, 1998)
Economics
2004-08-19
Keywords: Microeconomic; Economics - Mathematical; Consumer theory; Optimization; Partial equilibrium; Strategic behavior; Information economics